Tourism and technology - Ramos, Celia (2018)
Journeys for religious reasons has been occurring along the evolution of humanity, in more recent decades, some of these travels were motivated only by (religious) tourism reasons. The information and communications technologies (ICTs) has had much impact on tourism over time, because information is one of the most important aspects to consider in the tourism sector. ICT can contribute to greater and better dissemination of knowledge about tangible and intangible heritage, while potentiate the acquisition deeper knowledge by the tourist (or local). The sharing and dissemination of the heritage (religious) knowledge in general should nowadays be focus in all kind of users, from residents, to "traditional" tourists, including tourists with accessibility limitations, hearing and/or visual impairments, restricted mobility, etc., and special groups, like senior citizens and kids. In this context, this paper presents a methodological referential for the development of a system (application) that enhances the increase in tourist affective immersion with the displayed heritage and promoting his/her tourist experience, in a personal and spiritual level.